2023
DOI: 10.3390/foods12152869
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heat Treatment on the Structural and Functional Properties of Phaseolus vulgaris L. Protein

Abstract: The paper presents the effect of heat treatment at 80 °C at different times (3, 5, 7, and 9 min) on the structural and functional properties of Phaseolus vulgaris L. protein (PVP, bean protein powder). Surface and structure properties of PVP after heat treatment were analyzed using a Fourier transform infrared spectrometer (FTIR), a fluorescence spectrophotometer, a visible light spectrophotometer, a laser particle size analyzer, and other equipment. The secondary structure and surface hydrophobicity (H0) of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“… Cui et al, 2022a ), Phaseolus vulgaris L . protein (C. Li et al, 2023a , Li et al, 2023b ), corn protein (T. Song et al, 2021 ) and peanut protein ( Ning et al, 2020 ). In a study conducted by C. Li and colleagues in 2023 (C. Li et al, 2023a , Li et al, 2023b ), it was shown that heat treatment can expose Phaseolus vulgaris L .…”
Section: Preparation Methods Of Plant-based Protein Pickering Particlesmentioning
confidence: 99%
“… Cui et al, 2022a ), Phaseolus vulgaris L . protein (C. Li et al, 2023a , Li et al, 2023b ), corn protein (T. Song et al, 2021 ) and peanut protein ( Ning et al, 2020 ). In a study conducted by C. Li and colleagues in 2023 (C. Li et al, 2023a , Li et al, 2023b ), it was shown that heat treatment can expose Phaseolus vulgaris L .…”
Section: Preparation Methods Of Plant-based Protein Pickering Particlesmentioning
confidence: 99%
“…When subjected to heat, proteins undergo unfolding, thereby exposing hydrophobic groups within their structure and inducing functional changes. Li's research demonstrated that heat treatment heightened the foamability, emulsification, and digestibility of Phaseolus vulgaris L. protein ( Li, Tian, Liu, Dou, & Diao, 2023 ). Similar results have been extensively reported for soybean ( Liu et al, 2020 ) and pea proteins ( Shand, Ya, Pietrasik, & Wanasundara, 2007 ).…”
Section: Introductionmentioning
confidence: 99%